THE SIGNIFICANCE OF CHILDREN’S FOLK DANCES ACCOMPANIED BY SINGING IN THE PROCESS OF MUSIC TRADITION CONSERVATION AND FOSTERING - Aleksandar Stojadinović (Facta Universitatis. Series, Teaching, Learning and Teacher Education, 2017)
The crucial point this thesis is trying to answer is what concrete and practical possibilities there are nowadays in contemporary music culture teaching in the lower classes of primary school in order to implement and use children’s folk dances accompanied by singing, as well as what the aims, tasks and procedures are in the process of conservation and fostering of this form of national tradition. A teacher as a leader of the whole teaching process should tend to provoke joy, willingness and wish in his/her pupils to learn and practice children’s folk dances accompanied by singing, which can have an important impact on establishing a positive attitude to the values of traditional culture and art.